KERAGAMAN MORFOLOGI BAKTERI PENAMBAT NITROGEN DAN PELARUT FOSFAT DARI BERBAGAI LINGKUNGAN AGROEKOSISTEM DI KABUPATEN TAKALAR - Sangkala Sangkala; Ambri Bakhtiar; Elkawakib Syam’un (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This descriptive study aims to determine the morphological diversity of Nitrogen-fixing bacteria and Phosphate solubilizing bacteria from various agro-ecosystem environments in Takalar Regency. The research was done from September 2018 to April 2019. Soil samples were taken from dried land, irrigated rice fields, and rice fields of the south Galesong District. Colony morphology was isolated and characterized in the Laboratory of Bio-Science, Faculty of Agriculture, Hasanuddin University, and cell morphology was characterized in the Laboratory of Plant Diseases, Faculty of Agriculture, Universitas Brawijaya. The results showed variations in the morphological characteristics of the bacteria. Nitrogen-fixing bacteria isolates in irrigated rice fields were SIT02, PNSIT01, and PNSIT02, while the chili fields were PNTC01, PNTC02, and PNSIT02. Phosphate solubilizing bacteria in irrigated rice fields were SIT01, SIT03, SIT04, and SIT05, the chili fields were TC01 and TC02 isolates, and the dry land was TK01. The characteristics of Nitrogen-fixing bacteria isolates are round to stem, Gram-positive and negative, round to irregular colony shape, convex elevation, glossy surface, flat to choppy margins, and white to yellow. Phosphate-solubilizing bacteria are rod-shaped, gram-positive bacteria with a spherical colony form, convex to flat elevation, glossy surface, flat to wavy edges, and white color.